Anterior Locking Plate Osteosynthesis of Patellar Factures – Analysis of Complications and Functional Outcome - Tengler, Maxi Benita; Lill, Helmut; Wente, Maike; Ellwein, Alexander (Zeitschrift für Orthopädie und Unfallchirurgie, 2021)
Background Tension band wiring is the standard procedure for patellar fractures, but is associated with a high rate of implant related complications and implant failure. Tension band wiring may fail, especially with multifragmentary and comminuted fractures. Plate fixation of complex patellar fractures seems to be superior to wiring, both clinically and biomechanically. The aim of this study was to evaluate complications after locking plate fixation in patellar fractures two years after surgery and to access the functional outcome.Material and Methods As part of a prospective case series, all patients who had received locking plate fixation of a patellar fracture between April 2013 and May 2018 were clinically examined two years postoperatively and potential complications were evaluated.Results A total of 38 patients aged 19 – 87 years were included. Complications occurred in a total of five patients (13%), including one reactive prepatellar bursitis, one chronic infection and loss of reduction due to a dislocated pole fragment in three cases. The average active range of motion of the affected knee joint two years postoperatively was 133°. The Tegner activity scale score reached 3 points, the Lysholm score 95 points and the Kujala score 95 points.Conclusion With an overall relatively low complication rate and good clinical outcome, dislocated distal pole fragments are a common complication after plate fixation of patellar fractures. If preoperative diagnostic testing shows a pole fragment, a modified hook-plate can be used, with the possibility of fixing the pole fragment.Hintergrund Die Zuggurtungsosteosynthese als Standardverfahren von Patellafrakturen ist mit einer hohen Rate an implantatbezogenen Komplikationen und einer hohen Versagensrate assoziiert. Insbesondere mehrfragmentäre und Trümmerfrakturen können nicht adäquat versorgt werden. Die Plattenosteosynthese bei komplexen Patellafrakturen scheint biomechanisch und klinisch der Zuggurtung überlegen. Ziel der Studie war es, Komplikationen nach winkelstabiler Plattenosteosynthese bei Patellafraktur 2 Jahre postoperativ auszuwerten. Zudem wurde das funktionelle Ergebnis erfasst.Material und Methode Im Rahmen einer prospektiven Fallserie wurden alle Patienten, die zwischen April 2013 und Mai 2018 eine winkelstabile Plattenosteosynthese einer Patellafraktur erhalten hatten, 2 Jahre postoperativ klinisch untersucht sowie potenzielle Komplikationen ausgewertet.Ergebnisse 38 Patienten im Alter von 19 – 87 Jahren konnten eingeschlossen werden. Bei insgesamt 5 Patienten (13%) kam es zu Komplikationen, darunter eine reaktive Bursitis praepatellaris, ein chronischer Infekt und 3 Repositionsverluste bei proximalem oder distalem Polausriss. Der aktive Bewegungsumfang des betroffenen Kniegelenkes lag 2 Jahre postoperativ durchschnittlich bei 133°. Der Tegner-Aktivitätsscore erreichte 3 Punkte der Lysholm-Score lag bei 95 Punkten und der Kujala-Score erreichte 95 Punkte.Diskussion Bei vergleichbar niedriger Komplikationsrate und gutem funktionellen Outcome sind distale Polausrisse eine häufige Komplikation nach Plattenosteosynthese von Patellafrakturen. Wird präoperativ ein Polfragment erkannt, kann eine modifizierte Platte mit Haken zur Fixation eines Polfragmentes gewählt werden.
Keywords: multifragmentary patellar fracture; anterior locking plate fixation; tension band wiring; complication rate; displaced distale pole fragment